Achieving outstanding heat-resistant properties in Mg alloy via constructing stable solute-network. Issue 5 (4th May 2023) - Xie, Dongsheng; Pan, Hucheng; Pan, Zhen; Fu, Tong; Zeng, Zhuoran; Xie, Hongbo; Ren, Yuping; Tang, Weineng; Qin, Gaowu
Abstract : A new Mg–Sm–Ce–Mn-based alloying system with a large miscibility gap was uncovered, and multi-solute co-segregations at high-angular grain boundaries (HAGBs), dislocations and low-angular grain boundaries (LAGBs) are obtained after the proper extrusion process. During following long-term thermal exposure, the solute along HAGBs gradually evolves into nano-precipitates, while the precipitation process along LAGBs is obviously suppressed due to the intrinsically low-energy character, and numerous G. P. zones and γ" phases are formed in deformed regions, which always keep the limited size and reticular distribution. Consequently, the bimodal-grain structure is thermally stable, and the excellent high-temperature strength can be well maintained. GRAPHICAL ABSTRACT: UF0001 IMPACT STATEMENT: A new strategy of constructing a stable solute-network to achieve outstanding heat-resistant properties can be realized in low-alloyed Mg wrought alloy, and high-temperature UTS (∼291 MPa) can even exceed conventional Mg-RE alloys.